The Application of the Principle of Justice against the Criminal Acts of Religion Blasphemy - Jayu Praja (Budapest International Research and Critics University, 2022)
Indonesia is a pluralistic nation. This is because Indonesia consists of so many ethnic groups, languages, and so many religions that lived together even before Indonesia was born. Since the reformation era, there have been many cases of deviation, one of which is the case of blasphemy in various situations such as deviations in religious life. This can damage inter-religious harmony in society. One of the cases that will be analysed by the author in the context of compiling this thesis is case Number 53/Pid/2021/PT.DPS concerning blasphemy. The perpetrator of the crime is Lars Cristensen, a Danish citizen. The criminal act was committed by the perpetrator when he visited Ni Luh Sukerasih's house, then without the permission of the homeowner, the perpetrator committed a criminal act by destroying the place of prayer/pelinggih of the rock watchman belonging to Ni Luh Sukerasih. The act is carried out by kicking the place of prayer / religious guardian of the reef using the right foot which causes the upper part of the place of prayer to fall/collapse. Article IV paragraph 1 of Law no.1 of 1946 concerning criminal law. And the second violates article 156 letter of the Criminal Code. After the trial, the judge decided to jail for 7 years. The purpose of this study was to find out how the results of the trial of case no.32/PID.b/2002/Pn. Regarding the criminal act of blasphemy and how to analyze the elements of the indictment in Article 156 letter of the Criminal Code, the judge decided that the defendant was proven to have committed a crime in public by expressing feelings of hostility, hatred, or contempt for a group of Indonesian people, as stipulated in Article 156 of the Criminal Code.